Meditations on Asian Christian Spiritualities: A Multidisciplinary Response - Ruiz, Lester Edwin J. (Asia journal of theology, 2024)
This essay addresses the question, "Under what conditions is it possible to think about how one might address the challenges confronting the diverse descriptions, explanations, and understandings, as well as practices of Asian Christian spiritualities?" In seven intentionally unsystematic but related "meditations," and with the Asian Christian diaspora as its normative discursive horizon, the essay (1) addresses the multiple personal, political, historical, and religious contexts, locations, perspectives, and commitments of the author, (2) identifies some dilemmas, challenges, and perspectives in which the discourses of spirituality in Asia are embedded, (3) provides a diasporic perspective of "the body" as a metaphor for thinking through the notion of an Asian Christian spirituality, (4) explores the importance of social totalities, subjectivities, and practices for such discourses, (5) offers methodological and dispositional rituals to inform, orient, and emblematize practices for the reflective process (deliberation, embodying the res publica, and commitment to truthfulness), (6) explicates a materialist understanding of spirituality, and (7) proposes a detached transgressive spirituality with specific attention given to concerns about histories (time), geographies (space), and contextualities (place) of Asia- in-the-world. While not explicitly stated, the purpose of the essay is unabashedly partial: to reflect on the transformative significance of transcultural discourses for Asian Christian spiritualities, where transformation is understood as "the creation of the fundamentally new that is also fundamentally better."